Evaluasi Pelaksanaan dan Penerapan Prinsip dalam Pengelolaan Perusahaan yang Baik (Good Corporate Governance) pada PT Aneka Tambang Tbk - Iswandi Iswandi; Widya Rahmawati (Bina Nusantara University, 2011)
In terms of improving corporate performance and the efforts to create a healthy business climate, particularly in state-owned company, the application of the principles of good corporate governance (GCG) needs to be improved. Research conducted at PT Aneka Tambang Tbk is evaluating the application of the principles of GCG is in compliance with regulations applicable or not. In evaluating the data, the author uses descriptive method of research using a case study approach. The author gives a clear picture of the actual state of the object of research by looking at the facts that exist. After the data is obtained, the suitability evaluation based on several sources of theory relevant to the issues discussed. The authors collected data from PT Aneka Tambang Tbk through interviews and direct observation of the parties relating to corporate governance. Based on the evaluation, it can be concluded that PT Aneka Tambang Tbk has applied the principles of good corporate governance and in accordance with the existing parameters of the OECD 2004. With the application of a good and appropriate, effectivity and improved corporate efficiency and welfare of its employees, shareholders, and company stakeholders has also increased. In addition, the results of the evaluation stated that the consultation of shareholders against the company are very important stakeholders and should be maintained in order to create fluency in information exchange and exchange ideas effectively and efficiently.